1992
DOI: 10.1002/1097-0142(19921115)70:10<2381::aid-cncr2820701002>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Significance of glutathione S-transferase-π as a tumor marker in patients with oral cancer

Abstract: Background. The authors analyzed the clinical usefulness of glutathione‐S‐transferase‐π (GST‐π) as a tumor marker in patients with oral cancer. Methods. GST‐π levels in plasma of 61 patients with oral squamous cell carcinomas, 65 patients with benign oral diseases, and 78 healthy subjects were investigated with the sandwich enzyme‐immunoassay (EIA) system. Results. Elevated GST‐π levels in plasma were observed in patients with oral cancer, but patients with benign oral diseases had normal GST‐π levels. More th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 15 publications
0
28
2
Order By: Relevance
“…Moreover, the effects of CYP and GST polymorphisms on response were not observed to vary among the patients treated either with platinum and etoposide or platinum and other chemotherapeutics. These findings are likely to show that the studied CYP and GST polymorphisms are not functioning as a predictor of response to these two distinct platinum-based chemotherapy regimens, consisting of drugs among which namely cisplatin, carboplatin, etoposide and docetaxel are known substrates of especially GSTP1 enzyme [24,55,56], in advanced NSCLC patients. Our results are in line with those of Booton et al [39] who recently observed no association between the GSTP1 polymorphisms and platinum based treatment in advanced NSCLC patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of CYP and GST polymorphisms on response were not observed to vary among the patients treated either with platinum and etoposide or platinum and other chemotherapeutics. These findings are likely to show that the studied CYP and GST polymorphisms are not functioning as a predictor of response to these two distinct platinum-based chemotherapy regimens, consisting of drugs among which namely cisplatin, carboplatin, etoposide and docetaxel are known substrates of especially GSTP1 enzyme [24,55,56], in advanced NSCLC patients. Our results are in line with those of Booton et al [39] who recently observed no association between the GSTP1 polymorphisms and platinum based treatment in advanced NSCLC patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…In node-negative breast cancer increased GST acidic isoenzyme measured immunohistochemically was associated with decreased disease-free survival and overall survival (Gilbert et al, 1993), but there was no correlation between the level of GST isoenzyme expression and the length of disease-free survival in nodepositive breast cancer when the isoenzymes were quantified by Western blot (Peters et al, 1993). In gastric cancer an immunohistochemical study showed no significant correlation between GST acidic isoenzyme expression and clinicopathological features or prognosis (Okuyama et al, 1994), but in oral cancer the acidic isoenzyme was considered to be a useful aid to early diagnosis, prediction of disease extent and outcome (Hirata et al, 1992). Immunohistochemical measurements of neutral isoenzymes have shown a positive correlation with survival in childhood acute lymphoblastic leukaemia (Hall et al, 1994), and of acidic isoenzymes with survival in non-lymphoblastic leukaemia in adults (Koberda and Hellman, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The glutathione transferase enzymes are a group of cytosolic proteins capable of catalysing detoxification pathways involved in the breakdown of a number of chemotherapeutic agents (Mannervik and Danielson, 1988). Certain of the isoenzymes have been implicated as markers of early disease recurrence in nodenegative breast cancer (i isoenzyme) (Gilbert et al, 1993), squamous cell oral cancer (x isoenzyme) (Hirata et al, 1992), childhood acute lymphoblastic leukaemia (y isoenzyme) (Hall et al, 1994) and acute non-lymphoblastic leukaemia (7x isoenzyme) (Tidefelt et al, 1992).…”
mentioning
confidence: 99%
“…Hirata et al 13 had observed similar increase in the GTT activity, though the study was done using plasma. Integration of all these observation strengthens our thinking that elevation of salivary GTT in precancerous and cancerous conditions can be a reliable biomarker in early detection and prevention of oral malignancy.…”
Section: Discussionmentioning
confidence: 99%